PENGOLAHAN LIMBAH BAN BEKAS MENJADI KARYA DESAIN DI SENTRA WISATA BUKIT PECARINGAN - Eliapo Anwira; Dimitrij Ardian; Stephany Wirawan; Anik Juniwati (PeKA: Jurnal Pengabdian Kepada Masyarakat, 2022)
Through the service-learning program, students in the Sustainable Environmental Building class, Architecture Study Program, Petra Christian University collaborate with Village-own Enterprises (Badan Usaha Milik Desa) Makmur Bersinar Desa Jarak, recycled used materials into aesthetically functional objects for tourist facilities and infrastructure at Bukit Pecaringan Tourism Centre, Desa Jarak. Students designed and created sinks, swings, and piggybacks for the children's playground, and plant pots from end life tires. The utilization of end life tires be design work is an effort to take care of the environment. In this way, students learn to reduce the number of end life tires that increase yearly. This program and the design work of the waste became an aesthetic, functional object is an example to innovate for both other objects and purposes.